Genome-wide Identification and Evolution of the PP2C Gene Family in Eight Rosaceae Species and Expression Analysis Under Stress in Pyrus bretschneideri - Wang, Guoming; Sun, Xun; Guo, Zhihua; Joldersma, Dirk; Guo, Lei; Qiao, Xin; Qi, Kaijie; Gu, Chao; Zhang, Shaoling (Frontiers in Genetics, 2021)
Type 2C protein phosphatase (PP2C) plays an essential role in abscisic acid (ABA) signaling transduction processes. In the current study, we identify 719 putative PP2C genes in eight Rosaceae species, including 118 in Chinese white pear, 110 in European pear, 73 in Japanese apricot, 128 in apple, 74 in peach, 65 in strawberry, 78 in sweet cherry, and 73 in black raspberry. Further, the phylogenetic analysis categorized PbrPP2C genes of Chinese white pear into twelve subgroups based on the phylogenic analysis. We observed that whole-genome duplication (WGD) and dispersed gene duplication (DSD) have expanded the Rosaceae PP2C family despite simultaneous purifying selection. Expression analysis finds that PbrPP2C genes have organ-specific functions. QRT-PCR validation of nine PbrPP2C genes of subgroup A indicates a role in ABA-mediated response to abiotic stress. Finally, we find that five PbrPP2C genes of subgroup A function in the nucleus. In summary, our research suggests that the PP2C family functions to modulate ABA signals and responds to abiotic stress.